All about Eve [videorecording (DVD)] - Mankiewicz, Joseph L.; Davis, Bette, 1908-1989; Baxter, Anne; Monroe, Marilyn, 1926-1962; Sanders, George, 1906-1972; Orr, Mary (Studio classic, 2002)
From the moment she glimpses her idol at the stage door, Eve Harrington moves relentlessly towards her goal: taking the reins of power from the great actress Margo Channing. The cunning Eve maneuvers her way into Margo's Broadway role, becomes a sensation and even causes turmoil in the lives of Margo's director boyfriend, her playwright and his wife. Only the cynical drama critics see through Eve, admiring her audacity and perfect pattern of deceit.